RABIES IN JAFFRABADI BUFFALO- A CASE REPORT - Ahlawat, A R; Odedra, M D; Gajbhiye, P U (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Two cases of rabies in Jaffrabadi buffaloes at an organized farm are put on record for reference of field veterinarians.
Keywords: Rabies; pruritis